Development of Fertilizer Selection using Knowledge Management System - Yessy Yanitasari; Irman Hermadi; Wisnu Ananta Kusuma (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Fertilizer is a chemical substance or organism that has the role in supplying the nutrient substance to the plants directly or indirectly added to the soil in order for the plant to ordinary grow.  Much information on fertilizer is available on the internet, however the existence is still widely spread. Therefore, a forum to especially accommodate fertilizer selection using knowledge management system (KMS) is needed. In this research on fertilizer selection using knowledge management system is developed using the KMS Life Cycle (KMSLC) method, and implemented using Web based application. The knowledge in this system is obtained from expert explicit data entry and uploaded file from the users that has to be validated by an expert. The expert validation process is carried out with approval system, communication through messages and conversation. The outcome of the research is a web based application that was tried out by the users with good average tested value. DOI:  http://dx.doi.org/10.11591/telkomnika.v13i3.7224